Photodegradation of Rhodamine B over Biomass-Derived Activated Carbon Supported CdS Nanomaterials under Visible Irradiation - Huang, Hai-Bo; Wang, Yu; Cai, Feng-Ying; Jiao, Wen-Bin; Zhang, Ning; Liu, Cheng; Cao, Hai-Lei; Lü, Jian (Frontiers in Chemistry, 2017)
A family of new composite materials was successfully prepared through the deposition of as-synthesized CdS nanomaterials on lotus-seedpod-derived activated carbon (SAC). The SAC supports derived at different activation temperatures exhibited considerably large surface areas and various microstructures that were of great importance in enhancing photocatalytic performance of CdS@SAC composite materials toward the photodegradation of rhodamine B (RhB) under visible irradiation. The best-performing CdS@SAC-800 showed excellent photocatalytic activity with a rate constant of ca. 2.40 × 10−2 min−1, which was approximately 13 times higher than that of the CdS nanomaterials. Moreover, the estimated band gap energy of CdS@SAC-800 was significantly lowered down to 1.99 eV compared to that of the CdS precursor (2.22 eV), which suggested considerable strength of interface contact between the CdS and SAC support, as well as efficient light harvesting capacity of the composite material. Further photocatalytic study indicated that the SAC supports enhanced the separation of photogenerated electrons and holes in this system. Improved photocatalytic activity of the composite materials was largely due to the increased generation of catalytically active species such as h+, OH•, O2•- etc. This work provided a facile and low-cost pathway to fabricate photocatalysts for viable degradation of organic dye molecules.